PELEMBAGAAN PROGRAM BUDIDAYA LELE CORPORATE SOCIAL RESPONSIBILITY(CSR) PT KRAKATAU STEEL MELALUI PROSES KEMITRAAN DI KECAMATAN CITANGKIL, CILEGON - , ARFIAN WIBOWO J, Bahruddin,S.sos, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It is realized that big companies must take responsibility to the community and the environment. In the production process, companies must be producing excessive material that could disrupt human life and the environment in the area. Regarding this problem, PT Krakatau Steel as a state factory with Corporate Social Responsibility (CSR ) program or better known as Program Kemitraan dan Bina Lingkungan (The Partnership and Environment Development Program) is expected to be able to run the responsibility upon community and the environment related to the factoryâs output. The company holds a partnership program which one of those is to help people in catfish cultivation, both the fresh catfish and the proceeded one with more valuable selling price. This research sees how the institutionalization system of CSR program of PT Krakatau Steel to the community and the environment, particularly the assisted partner of the catfish cultivation. Self-reliance and the empowerment of the community who have received the CSR program interest the researcher. The method used in this research is the qualitative research method. The data used are primary and secondary data. Field observation was held to gain the primary data through interviews and observations. Secondary data obtained from bibliographical studies and documentation. Informants in this research are 10 people, 2 of them are employees of PKBL division of PT Krakatau Steel, 3 people are the government officials, the other 3 are assisted partners, one person is the community representative, and the other one is personnel of Cilegon Corporate Social Responsibility (CCSR). As the result of the research, it is known that the institutionalization system of the Corporate Social Responsibility program of PT Krakatau Steel still not yet appropriately walked to the institutionalization stage it self. Found problem is the lacking of the human resources of the PKBL division of PT Krakatau Steel that leads to a less effective in distribution and monitoring system. On the other hand, the facilities given by the company such as training and marketing werenât distributed throughout the assisted partners. This makes some of them forced to gain knowledge and running the business on their own with favors of their own family. The companyâs loss also inflicts lack of fund for the CSR program with the inactivation of the partnership program could not be avoided at the end of 2013 as the consequence.